Characterization of morphological conversion of Helicobacter pylori under anaerobic conditions. (26th April 2018) - Hirukawa, Sayaka; Sagara, Hiroshi; Kaneto, Satoshi; Kondo, Tomoyo; Kiga, Kotaro; Sanada, Takahito; Kiyono, Hiroshi; Mimuro, Hitomi
ABSTRACT: Helicobacter pylori ( H. pylori ), a gram‐negative microaerophilic bacterial pathogen that colonizes the stomachs of more than half of all humans, is linked to chronic gastritis, peptic ulcers and gastric cancer. Spiral‐shaped H. pylori undergo morphologic conversion to a viable but not culturable coccoid form when they transit from the microaerobic stomach into the anaerobic intestinal tract. However, little is known about the morphological and pathogenic characteristics of H. pylori under prolonged anaerobic conditions. In this study, scanning electron microscopy was used to document anaerobiosis‐induced morphological changes of H. pylori, from helical to coccoid to a newly defined fragmented form. Western blot analysis indicated that all three forms express certain pathogenic proteins, including the bacterial cytotoxin‐associated gene A (CagA), components of the cag ‐Type IV secretion system (TFSS), the blood group antigen‐binding adhesin BabA, and UreA (an apoenzyme of urease), almost equally. Similar urease activities were also detected in all three forms of H. pylori . However, in contrast to the helical form, bacterial motility and TFSS activity were found to have been abrogated in the anaerobiosis‐induced coccoid and fragmented forms of H. pylori . Notably, it was demonstrated that some of the anaerobiosis‐induced fragmented state cells could be converted to proliferation‐competent helical bacteria in vitro . These results indicate that prolonged exposure to the anaerobic intestine may not eliminate the potential for H. pylori to revert to the helical pathogenic state.